STABILITY-INDICATING METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF CABOZANTINIB IN PHARMACEUTICAL DOSAGE FORMS BY ULTRA-PERFORMANCE LIQUID CHROMATOGRAPHY - Ashok, Gorja; Mondal, Sumanta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The proposed study aimed to develop a stability-indicating ultra-performance liquid chromatography (UPLC) method for the estimation of cabozantinib in pharmaceutical dosage form and validate the method in accordance with the International Conference on Harmonization guidelines. Methods: The optimized conditions for the developed UPLC method are Acquity UPLC Hibar C18 (100 mm Ã— 2.1 mm, 1.7 Î¼) column maintained at 30Â°C with mobile phase consisting of 0.1% orthophosphoric acid and acetonitrile in the ratio of 55:45% v/v on isocratic mode at flow rate of 0.3 mL/ min. The sample was detected at 244 nm. Results: The retention time for cabozantinib was deemed 1.3 min. The developed method was validated for accuracy, precision, specificity, ruggedness, robustness, and solution stability. The method obeyed Beer's law in the concentration range of 20 Î¼g/mL and 120 Î¼g/mL with correlation coefficient of 0.9997. Forced degradation studies were conducted by exposing the drug solution to numerous stress conditions such as acidic, basic, peroxide, neutral, photolytic, and thermal conditions. The net degradation was considered within the limits, indicating that drug is stable in stressed conditions. Conclusion: The developed method for the estimation of cabozantinib can be utilized for the routine analysis of pharmaceutical dosage form.